A Review of Smart Metering for Future Chinese Grids. (October 2018) - Wang, Yikuai; Qiu, Huadong; Tu, Ying; Liu, Qiang; Ding, Yi; Wang, Weifeng
Abstract: Smart metering solutions are crucial to the future power grid infrastructure. In order to develop next generation of metering system in Chinese smart grid, this research investigates smart metering in industrial perspectives, focusing on mainstream international metering technologies. Especially, to meet with the time and qualification requirements of the start-up period of developing spot market, the study applies economic mathematical method to estimate smart metering updating project.